Chin asymmetry perception among orthodontists, general dentists, and laypersons - Prajwal Prabhu; G Shivaprakash; Afshan Saman Waremani; Ayush Dixit; B R Kavya; G Shivaprasad (Journal of Orthodontic Science)
BACKGROUND: Contemporary society places a strong emphasis on the importance of facial esthetics. This perception of esthetics is inherently related to facial symmetry. Esthetics of soft tissues plays an important role in the selection of the therapeutic strategy; thus, the subjective evaluation of chin asymmetry is of great significance for clinical treatment. AIM: The objective of the study is to evaluate: 1. The degree of chin asymmetry on esthetics perception in frontal view and 2. To analyze the critical evaluation of chin asymmetry by dental professionals and laypersons with frontal facial photographs. METHODOLOGY: Chin asymmetries were analyzed through a series of edited frontal photographs of two subjects (male and female). The position of the chin was digitally altered from 0° (no alteration) to 6° (most severe alteration). Participants’ responses were collected from laypersons (n = 100), general dentists (n = 50), and orthodontists (n = 51), and the photographs were graded according to esthetic appeal using a visual analog scale. Statistical analysis showed the diagnostic threshold levels for identifying chin asymmetries. RESULTS: General dentists and laypersons showed similar threshold for diagnosing chin asymmetry in male and female subjects of 4°, whereas orthodontists could diagnose transverse chin asymmetry in male and female subjects at a 3° deviation. All the groups rated the 0° and 1° as the most attractive and 5° and 6° as the least attractive. CONCLUSIONS: Laypersons and general dentists had a relatively same accuracy in diagnosing transverse chin asymmetries in both female and male subjects, whereas orthodontists have relatively higher accuracy compared with other groups.